A hierarchical porous ionic organic polymer as a new platform for heterogeneous phase transfer catalysis. Issue 47 (4th November 2015) - Sun, Qi; Ma, Shengqian; Dai, Zhifeng; Meng, Xiangju; Xiao, Feng-Shou
Abstract : A hierarchical porous ionic polymer with excellent amphiphilicity has been successfully constructed and demonstrates extraordinary performances as a heterogeneous phase transfer catalyst. Abstract : In this work we demonstrate for the first time the construction of a hierarchical porous ionic organic polymer via the polymerization of the vinyl-functionalized quaternary phosphonium salt monomer under solvothermal conditions. The resultant polymerized quaternary phosphonium (PQP) salt features a hierarchical porous structure and excellent amphiphilicity. After anion-exchange with peroxotungstate, the afforded W2 O11 /PQP demonstrates excellent performances as a heterogeneous phase-transfer catalyst in the context of epoxidation of olefin and oxidation of dibenzothiophene when using the environmentally benign H2 O2 as the oxidant, superior to the homogeneous counterparts and other types of phase-transfer catalysts. Our work thereby paves a way to advance hierarchical porous ionic organic polymers as a new type of platform for heterogeneous phase transfer catalysis.